Teaching English via corpus concordancing in a Greek university - Argyroulis, Vassilis (2017)
This thesis focuses on teaching English via corpus concordancing in a Greek university and is motivated by a need to find an improved approach to teaching and learning English for Specific/Academic Purposes so that university students improve their English language skills and motivation. I assemble a corpus of thirty million words containing texts from the domains of Special Education, General Academic, and General English. I compare and contrast a corpus teaching method (CTM) to a traditional teaching method (TTM) in terms of student performance in linguistic tasks and student motivation. I particularly explore (1) the extent to which CTM is more effective than TTM with regard to student performance as measured by the overall percentage of correct responses in student performance tasks, (2) the extent to which the effectiveness of CTM with regard to student performance on performance tasks is moderated by the ability level of the student (beginner, intermediate, advanced), (3) the extent to which the effect of method on student performance is mediated by student motivation after controlling for student level, and (4) what it is that motivates university students in Greece when involved in corpus concordancing compared and contrasted with existing traditional practice in learning English. Apart from performance measurement by percentage in four linguistic tasks assigned to students in the quantitative portion of this thesis, further data collection procedures to estimate motivation were item analyses of two motivational questionnaires, one about the contrast between CTM and TTM and one about the corpus concordancing software used in this study. The qualitative portion employs the use of an open-ended survey with five questions about CTM and TTM and a corpus style analysis of the survey. The objective of the qualitative part is to determine to what extent student motivation informs students’ preferred teaching style when asked to compare CTM and TTM, and to identify motivational and demotivational factors when using the one learning method or the other. The quantitative and qualitative findings are triangulated in order to validate interpretations. Key points of convergence between the quantitative and qualitative results are identified, which allowed a description of key student benefits and difficulties when CTM is used. An analysis of benefits and difficulties constituted the basis for the development of a suggested teaching unit to be utilized by teachers of English at university level. I demonstrate that CTM is more effective than TTM in the student performance tasks and that CTM is effective across all student ability levels with the advanced students performing better than the intermediate and beginner students. I also demonstrate that the sample of students was more motivated to learn English via CTM than via TTM and that student general motivation is a mediator in terms of the relationship between the teaching method and student performance. Finally, I demonstrate important features that motivate or demotivate students when following CTM or TTM. Based on the overall findings, I recommend a CTM exemplary teaching unit to be used by teachers who teach English at tertiary level. This thesis also offers useful guidance and practice to teachers of English and students on how to make use of a corpus concordancing software program to fulfil their teaching and learning purposes, respectively.